Exploring Consumer’s Propensity to Consume Insect-Based Foods. Empirical Evidence from a Study in Southern Italy - Elena Arena; Agata Mazzaglia; Roberta Selvaggi; Biagio Pecorino; Biagio Fallico; Mattia Serranò; Gioacchino Pappalardo (Applied System Innovation, 2020)
While admitting that neophobia and sociocultural factors negatively affect consumers’ propensity to consume insect-based foods, other aspects related to food values that consumers attach to these foods could have an influence on consuming decision. In order to identify the motivations and determinants that influence the propensity to consume insects and then to explore the drivers behind consumers’ willingness to consume insect-based foods, the data collected through the questionnaire were processed. After a descriptive analysis of the data, ANOVA was performed. Moreover, Student’s t test and pairwise correlation indices were estimated in order to determine statistically significant correlation. Our findings show that information about edible insects brought about an increase in food neophobia and appearance affected the expected liking levels. In addition, we have shown that respondents’ propensity to consume insect-based foods also depends on consumers’ subjective beliefs about food values such as healthiness, naturalness and environmental impact. We also found that respondents’ beliefs about food values associated with insect-based foods do not depend on the degree of information provided but are probably due to pre-existing prejudices about them.